Germline TP53 pathogenic variants and breast cancer: A narrative review. (March 2023) - Blondeaux, Eva; Arecco, Luca; Punie, Kevin; Graffeo, Rossella; Toss, Angela; De Angelis, Carmine; Trevisan, Lucia; Buzzatti, Giulia; Linn, Sabine C.; Dubsky, Peter; Cruellas, Mara; Partridge, Ann H.; et al.
Highlights: Penetrance and phenotype of the TP53 pathogenic variant should be considered. Tumor biology should be incorporated in the criteria for offering TP53 testing. Mastectomy should be preferred to lumpectomy and radiotherapy avoided. Risk-reducing contralateral mastectomy should be discussed. Collaborative research efforts are strongly encouraged. Abstract: Approximately 10% of breast cancers are associated with the inheritance of a pathogenic variant (PV) in one of the breast cancer susceptibility genes. Multiple breast cancer predisposing genes, including TP53, are responsible for the increased breast cancer risk. Tumor protein-53 ( TP53 ) germline PVs are associated with Li-Fraumeni syndrome, a rare autosomal dominant inherited cancer predisposition syndrome associated with early-onset pediatric and multiple primary cancers such as soft tissue and bone sarcomas, breast cancer, brain tumors, adrenocortical carcinomas and leukemias. Women harboring a TP53 PV carry a lifetime risk of developing breast cancer of 80–90%. The aim of the present narrative review is to provide a comprehensive overview of the criteria for offering TP53 testing, prevalence of TP53 carriers among patients with breast cancer, and what is known about its prognostic and therapeutic implications. A summary of the current indications of secondary cancer surveillance and survivorship issues are also provided. Finally, the spectrum of TP53 alteration and testing is discussed. The optimal strategies for the treatment of breast cancer in patients harboring TP53 PVs poses certain challenges. Current guidelines favor the option of performing mastectomy rather than lumpectomy to avoid adjuvant radiotherapy and subsequent risk of radiation-induced second primary malignancies, with careful consideration of radiation when indicated post-mastectomy. Some studies suggest that patients with breast cancer and germline TP53 PV might have worse survival outcomes compared to patients with breast cancer and wild type germline TP53 status. Annual breast magnetic resonance imaging (MRI) and whole-body MRI are recommended as secondary prevention.